Multivalvular involvement associated with Libman-Sacks endocarditis detected by multimodality imaging: A case report - Bui, Son Tran Thanh; Nguyen, Phuong Hoang; Nguyen, Trang Ngoc; Kirkpatrick, James N.; Nguyen, Viet Khoi; Nguyen, Hoai Thi Thu (Frontiers in Cardiovascular Medicine, 2023)
Libman-Sacks endocarditis accounts for 6–11 percent of systemic lupus erythematosus patients and is associated with varying degrees of valvular dysfunction, increased risk for stroke and transient ischemic attacks, and increased mortality. In previous studies, left-sided valvular Libman-Sacks vegetations were more frequently detected than right sided vegetations; reported cases of bilateral involvement is very rare. A comprehensive clinical assessment and the multimodality imaging is of utmost importance in the management of systemic lupus erythematosus. In this case report, we describe a 31-year-old female patient with uncontrolled systemic lupus erythematosus initially presented with gastrointestinal symptoms but eventually had a vegetation-like structure on the posterior leaflet of the mitral valve which was revealed during routine echocardiography. Two-dimensional/three-dimensional transthoracic and transesophageal echocardiography, cardiac magnetic resonance, and cardiac computed tomography further characterized the mitral valve vegetation and revealed an additional vegetation of the pulmonary valve. Echocardiography remains the cornerstone for the detection of Libman-Sacks vegetations. Cardiac MRI and cardiac CT are useful in characterizing lesion size and effects and may prove particularly helpful in the assessment of right-sided or multivalvular endocarditis. The presence of focal brain lesions on brain MRI prompted antithrombotic therapy.